2003
DOI: 10.1093/ndt/gfg373
|View full text |Cite
|
Sign up to set email alerts
|

Renal transplantation in patients with primary immunoglobulin A nephropathy

Abstract: Our data suggested that around one-fifth of patients with primary IgAN developed recurrence by 5 years after transplantation. Recurrent IgA nephropathy in allografts runs an indolent course with favourable outcome in the first 12 years. However, the contribution of recurrent disease to graft loss becomes more significant on long-term follow up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
68
4
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 15 publications
6
68
4
3
Order By: Relevance
“…In the Australia-New Zealand registry, the long-term graft survival was not affected by the increased risk of recurrence in zero-mismatched kidneys (17). In two large Asian reports, the risk of graft loss due to recurrence ranged around 3% to 4% (18,19). However, in the very long term it is possible that recurrent IgAN may represent a substantial risk factor for graft failure.…”
Section: Iganmentioning
confidence: 99%
“…In the Australia-New Zealand registry, the long-term graft survival was not affected by the increased risk of recurrence in zero-mismatched kidneys (17). In two large Asian reports, the risk of graft loss due to recurrence ranged around 3% to 4% (18,19). However, in the very long term it is possible that recurrent IgAN may represent a substantial risk factor for graft failure.…”
Section: Iganmentioning
confidence: 99%
“…Although we do not know the natural course of this patient's IgA nephropathy, recurrent IgA nephropathy generally runs an indolent course with favorable outcome in the first 12 years [6], which contrasts with the observed rapidly progressive course just 3 years post transplant. Third and most interestingly, our patient developed impaired renal function, hypertension and nephrotic-range proteinuria shortly after anti-VEGF therapy began, whereas these disorders improved upon its withdrawal.…”
Section: Discussionmentioning
confidence: 57%
“…In those cases, the recurrence rate was between 12.5 and 50%. [6] Importantly, it was found that 52% of the IgAN recurrences diagnosed by protocol biopsies were not accompanied by proteinuria or hematuria. Thus, protocol biopsies with immunofluorescence analysis constitute an essential tool for the diagnosis of recurrence, even if it is clinically silent [7].…”
Section: Discussionmentioning
confidence: 99%